Critical analysis of funding issues in public schools of KwaZulu-Natal - Mbokazi, Msawenkosi Sandile; Lebeloane, Lazarus Donald Mokula (Journal of Economic Development, Environment and People, 2025)
This article provides a comprehensive discussion and analysis of the funding challenges faced by public schools in KwaZulu-Natal. The KwaZulu-Natal Department of Education is currently confronting significant financial hurdles that are adversely affecting schools across the region. Key issues include reduced funding, delayed payments, and a critical shortage of resources for essential supplies and infrastructure. As a result, schools are experiencing operational difficulties that undermine the quality of education for both educators and students, ultimately affecting the overall standard of learning. Employing an interpretivist approach and qualitative research methods, the study involved interviews with four union office-bearers and ten school principals who are actively engaged in the management of school finances. The findings indicate a clear financial crisis within schools in the province. Funds are disbursed in tranches, leading to instability as the allocated amounts prove insufficient to cover operational expenses and repay existing debts, resulting in a lack of basic resources. Many schools have accrued significant debts, leaving them uncertain about how to address these obligations. In some cases, principals have had to use personal finances to cover school expenses. To tackle these pressing issues, the study recommends a strategic reallocation of resources to prioritise critical areas in education, such as acquiring Learner-Teacher Support Materials, securing funding for necessary services, and ensuring that teacher retention remains a top priority. Additionally, school governing bodies should actively participate in fundraising efforts and implement cost-saving measures to support their institutions.